Pengaruh Perbedaan Suku Bunga, Margin Bunga Bersih, Kredit Bermasalah, Rasio Kecukupan Modal, Dana Pihak Ketiga dan Pendapatan Berbasis Biaya terhadap Profitabilitas Bank - Bayu Dwiputranda Perkasa (Sekolah Pascasarjana Perbanas Jakarta, 2020)
Third-Party Funds and Fee-Based Income on Bank Profitability. The independent variables used in this study consisted of the Influence of Interest Rate Spread, Net Interest Margin, Non-Performing Loans, Capital Adequacy Ratio, Third Party Funds and Fee-Based Income on Bank Profitability. In contrast, the dependent variable was ROA and ROE. The study investigates the effect of the independent variables on the dependent variable. There are ten national and private commercial banks as a sample. The method of analysis uses panel regression analysis. The results show that the interest rate, NPL, and Fee-based income spreads partially have no significant effect on ROA and ROE. NIM partially has a significant effect on ROA but does not have a significant effect on ROE. CAR does not have a significant effect on ROA but has a significant effect on ROE. Deposits have no significant effect on ROA but have a significant effect on ROE. Spread of Interest Rate, Net Interest Margin, Non-Performing Loans, Capital Adequacy Ratio, Third Party Funds and Fee-Based Income influence ROA and ROE, with a coefficient of determination of 83.42% and 83.53%, respectively.